Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1175/2011jcli4129.1
|View full text |Cite
|
Sign up to set email alerts
|

Teleconnection Pathways of ENSO and the IOD and the Mechanisms for Impacts on Australian Rainfall

Abstract: Impacts of El Niñ o-Southern Oscillation (ENSO) and the Indian Ocean dipole (IOD) on Australian rainfall are diagnosed from the perspective of tropical and extratropical teleconnections triggered by tropical sea surface temperature (SST) variations. The tropical teleconnection is understood as the equatorially trapped, deep baroclinic response to the diabatic (convective) heating anomalies induced by the tropical SST anomalies. These diabatic heating anomalies also excite equivalent barotropic Rossby wave trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
337
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 398 publications
(360 citation statements)
references
References 33 publications
23
337
0
Order By: Relevance
“…These AGCM experiments seem to indicate that western Indian Ocean SSTs are not crucial in varying Australian climate, as seen mediated through the Rossby wave train in observations (Cai et al 2011). The emphasis on eastern Indian Ocean SST, as included in the N w /N c cases, instead agrees with Ummenhofer et al (2009), who showed that rainfall across southern regions of Australia is modulated by the meridional gradient in eastern Indian Ocean SST, with little effect in response to western Indian Ocean SST anomalies.…”
Section: B Western Indian Ocean Sstsupporting
confidence: 51%
See 2 more Smart Citations
“…These AGCM experiments seem to indicate that western Indian Ocean SSTs are not crucial in varying Australian climate, as seen mediated through the Rossby wave train in observations (Cai et al 2011). The emphasis on eastern Indian Ocean SST, as included in the N w /N c cases, instead agrees with Ummenhofer et al (2009), who showed that rainfall across southern regions of Australia is modulated by the meridional gradient in eastern Indian Ocean SST, with little effect in response to western Indian Ocean SST anomalies.…”
Section: B Western Indian Ocean Sstsupporting
confidence: 51%
“…The role of anomalous SST in the western Indian Ocean for Australian climate has been raised previously as a means of transmitting ENSO and Indian Ocean dipole impacts onto extratropical Australian rainfall, mediated through Rossby wave trains (Cai et al 2011). Here, we explore the effect of western Indian Ocean SST on Rossby wave trains and blocking in the AustraliaNew Zealand sector further: in the 100-yr simulations WIO w and WIO c , warm/cold SST anomalies were superimposed over the western Indian Ocean within 58N-128S, 408-908E (Fig.…”
Section: B Western Indian Ocean Sstmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to see that the IOD signal still has a strong sea level anomaly in DJF despite the fact that it disappears from the SST in December (Saji et al 1999;Hendon et al 2012). Whilst the IOD covaries strongly with ENSO in austral spring (Lim et al 2009b;Cai et al 2011) and rapidly terminates as the Australian monsoon develops in the austral early summer season , it evidently still persists in the subsurface, affecting the SLA at the eastern and western boundaries of the Indian Ocean. In addition, EOF1 has a strong signature of a variable strength Leeuwin current along the West Australian coastline associated with ENSO.…”
Section: Observation Comparisonmentioning
confidence: 99%
“…The large-scale atmospheric circulation over this region plays an important role in not only influencing the variability of the tropical climate systems but also transferring their impacts remotely through teleconnections (Wang and Zhang 2002;Cai et al 2011;Sun and Zhou 2013). Within the tropical Indo-Pacific domain, the low-level atmospheric circulation plays a major role in facilitating the intensive ocean-atmosphere interactions.…”
Section: Introductionmentioning
confidence: 99%